To investigate the role of Memantine as anxiolytic in elevated plus maze test and as antidepressant in tail suspension test in Swiss albino mice - Bagewadi, Harish G.; Venkatadri, T. V.; Rajeshwari, B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The magnitude of improvement seen with present conventional medicines for anxiety and depression remain disappointing thereby providing a scope for the study of newer drugs. In the literature, there is evidence demonstrating the modulation of N-methyl-D-aspartate (NMDA)receptors in anxiety and depression. The present study is undertaken to evaluate the antianxiety effect of memantine in elevated plus maze (EPZ) test and its antidepressant effect in tail suspension test (TST)in Swiss albino mice. Methods: Animals were divided into six groups (n=6). First group mice were given normal saline (10 ml/kg), second group were administered lorazepam (0.5 mg/kg), third group with memantine (3 mg/kg) and fourth group with memantine plus lorazepam, fifth group was administered amitriptyline (10 mg/kg)and sixth group received memantine plus amitriptyline. All drugs were administered by intraperitoneal route daily for 7 consecutive days. Results were analyzed by one-way ANOVA followed by post-hoc Tukey’s test. Results: Memantine treated mice showed significant increase (p<0.001)in time spent and number of entries in open arm and significant decrease in time spent and number of entries in closed arm in EPZ when compared to control group. Duration of immobility was significantly (p<0.001)reduced in animals treated with memantine when compared to the control group in TST. Conclusions: NMDA antagonist, memantine has showed significant antianxiety effect in EPZ test and antidepressant effect in TST.